A Review of Journal of Indian Law Institute in Legal Education. (January 2017) - Sharma, Prakash
The aim of this review is to document a range of articles which were published by the esteemed institution established solely for the purpose of legal education (LE) and research—Indian Law Institute (ILI). So far, the experts and scholars have remained pessimistic about the direction of LE in India. The work acknowledges that though there were multiple understandings of various aspects pertaining to LE in India and abroad, the same were not found to be of any relevance. This review addresses how an ideal system of law must draw its postulates and legal justification from science. A particular focus was given on the prestige and the quality of institutions imparting LE. In addition to describing problems, efforts have been made to suggest some initiatives towards making an effective use of various available opportunities. The context of the review only adds to the relevance of this exercise. Apart from the dynamic character of our legal environment and the ambition to benefit from the developments in the technological world, which has contributed to social growth, we have discovered that this environment is more vulnerable than what most people had assumed.